Productivity Spillovers in Team Production: Evidence from Professional Basketball - Arcidiacono, Peter; Kinsler, Josh; Price, Joseph (Journal of Labor Economics, 2017)
We estimate a model where workers are heterogeneous both in their own productivity and in their ability to facilitate the productivity of others. We use data from professional basketball to measure the importance of peers in productivity because we have clear measures of output and members of a worker’s group change on a regular basis. Our empirical results highlight that productivity spillovers play an important role in team production. Despite this, we find that worker compensation is largely determined by own productivity with little weight given to productivity spillovers.